"Transcendence" Between Anthropology and Metaphysics: A Concept in Need of Rethinking - Puntel, Lorenz B. (Archīum Ateneo, 2024)
"Transcendence" Between Anthropology and Metaphysics: A Concept in Need of Rethinking